Effect of Botanical Extract on Pest Control in Brinjal Field (Journal of Environmental Science and Natural Resources, 2013)
An experiment was conducted to evaluate the effect of eight botanical extracts on pest control in brinjal field. Accordingly, water extracts of dried leaves of Khuksa (Ficus hispida), Chotra (Lantana sp.), Chirata (Swietia chrata), Neem (Azadiracta indica), Bael (Aegle marmelos), Holde-hurhuri (Cleomp viscosa) and Marigold (Targetes erecta) and seeds of Mahogany (Swietenia mahagoni) were prepared and sprayed in experimental brinjal field at Rajshahi University. Out of these botanicals, Khuksha leaves extract showed best performance against the pest attack compare to other extracts. Marigold leaf extract also showed good performance in the protection of brinjal plant from pest. The efficacy of Chotra, and Chirata leaf extracts was nearly same in brinjal plot against the pest attack. Neem leaf extracts showed moderate performance against pest. Mahogany seed extract showed lowest efficacy and hampered the normal plant growth and caused fruit rottening as well as reduced the yield of brinjal. Although Khuksha, Beal and Marigold leaf extracts were found effective against brinjal pests but a higher production was observed in the treatments of Neem and Chirata leaf extracts in experimental brinjal field.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14809 J. Environ. Sci. & Natural Resources, 5(2): 173-176 2012